Javanese Art’s Therapy Sebagai Intervensi Menurunkan Tingkat Depresi Lansia di Panti Wreda Harapan Ibu Semarang - I Putu Krisna Widya Nugraha; Hellen Marini; Utami Dwi Yusli; Anteng Ambarwati; Ika Rahmawati (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2017)
The most common health problem among the elderly is depression, which is characterized by extreme sadness, low interest in performing the activity and an inability to feel happiness. One of the causes of this depression is due to the psychological factors, such as social support. The Javanese Art’s Therapy in the form of Group Activity Therapy (GAT) is an alternative that can be used to deal with the depression problem. This community service program aimed to provide coaching on depression therapy through a combination of dance and gamelan music to reduce the level of depression among elderly. The method included the provision of health education, implementation of GAT, and evaluation. The program involved 42 elderly at Harapan Ibu Nursing Home in Semarang. Pre-test was done to 22 elderly from 42 elderly with result 15 depressed elderly. The health education about depression was given to the elderly and caregivers using the picture media. The GAT was administered for 30 minutes in 2 sessions; each lasted for 15 minutes. Meanwhile, the evaluation was carried out by assessing the elderly’s feelings by using the Geriatric Depression Scale (GDS) instrument. The GAT of Javanese Art’s Therapy could reduce the level of depression among the elderly at Harapan Ibu Nursing Home in Semarang.